The prevalence, classification, and potential clinical implications of anatomical variations of first cervical vertebra: A computed tomographic study - Priyanka Pandey; Swati Yadav; Navbir Pasricha; Shamrendra Narayan (Wolters Kluwer Medknow Publications, 2023)
Background: First cervical vertebra has different anatomical features than other cervical vertebrae. It holds globe of skull and lacks body and spine. It is composed of 2 lateral masses linked by anterior and posterior arches. Posterior atlanto-occipital membrane is attached to posterior arch whose lateral edge sometimes ossifies thus converting groove into canal. Consequently, neurovascular groove gets converted into a bony ring "ponticulus posticus". It can cause of neck pain and headache. Knowledge of this variation is important during various orthopedic procedures involving atlas including C1 lateral mass screw placement.Congenital defects of atlantal arch a developmental failure of chondrogenesis is a rare anomaly. These defects are a benign variation discovered incidentally. Detection of these anomalies is clinically important as they can cause acute neurologic deficits, which is associated with neck extension. Study was done: To determine the prevalence of Ponticulus Posticus and to report the frequency of various types of congenital malformations of the atlantal arch. Methodology: 250 computerized tomography (CT) head and neck in axial and sagittal sections from Picture Archiving and Communication System (PACS) of Dr RMLIMS, Lucknow was studied as CT is the best method to study the bony landmarks and any anomaly. Prevalence of variations was calculated. Data was analyzed statistically using SPSS version 21 by Chi-square test. Result: Prevalence of ponticulus posticus was 32.4%. Males had higher prevalence (20.4%) than females (12%). Incomplete ponticulus posticus (24.4%) was more than complete variant (8%). There was predominance of left sided ponticulus posticus(12% vs 8.4%) Deficient posterior arch was found in 9(3.6%) cases. 6 were of type A 3 were of type B. Conclusion: This study will help in determining cause of neurological deficit in patients due to presence of above variations.